2004
DOI: 10.1093/mutage/geh007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo genotoxicity of cypermethrin in Drosophila melanogaster using the alkaline Comet assay

Abstract: The single cell gel electrophoresis (SCGE) assay, also known as the Comet assay, is one of the most promising genotoxicity tests developed in recent years to measure and analyse DNA damage in single cells. The present study was undertaken to assess the in vivo genotoxicity of the synthetic pyrethroid cypermethrin in brain ganglia and anterior mid gut of Drosophila melanogaster. Freshly emerged first instar larvae (22 +/- 2 h) were placed in different concentrations of cypermethrin (0.0004, 0.0008, 0.002, 0.2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 41 publications
3
65
0
Order By: Relevance
“…The comet assay is one of the most promising genotoxicity tests developed to measure and analyze DNA damage in single cells (Mukhopadhyay et al, 2004). The test was used as a parameter for assessing the DNA damage index ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…The comet assay is one of the most promising genotoxicity tests developed to measure and analyze DNA damage in single cells (Mukhopadhyay et al, 2004). The test was used as a parameter for assessing the DNA damage index ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…These results may be due to DNA repair occurred which differ from the study of Yousef et al (2010) that there were a higher DNA damage in the mature adults with respect to the long period of feeding of Shistocerca gregaria on clover treated with CdCl 2 and PbCl 2 reflects the absence of repair mechanism. But there are many studies used the comet assay to observe DNA repair in irradiated cells (Isabel and Maria, 2014) and in different cells of Drosophila after exposure to different genotoxic agents (Bilbao et al, 2002;Mukhopadhyay et al, 2004;Siddique et al, 2005bSiddique et al, , 2013García -Sar et al, 2012;Sharma et al, 2012;Mishra et al, 2014;Gaivã o et al, 2014;Isabel and Maria, 2014).…”
Section: Genotoxicity and Dna Repairmentioning
confidence: 99%
“…While most of the studies reported so far describe damage in brain cells of the fly, this study and earlier studies from this laboratory [Siddique et al, 2003;Mukhopadhyay et al, 2004] indicate that gut cells also are useful for studying DNA damage and repair.…”
Section: Discussionmentioning
confidence: 51%
“…For each treatment group, slides were prepared in duplicate according to the method of Mukhopadhyay et al [2004]. The cell suspension (80 ll) was mixed with 80 ll of 1.5% low melting point agarose (final concentration 0.75%).…”
Section: Evaluation Of Dna Damage By Comet Assaymentioning
confidence: 99%